Geotechnical investigation for the emplacement of radio telemetry dishes at the Matjiesfontein Space Geodesy observatory - Coetzee, Jaco (Stellenbosch : Stellenbosch University, 2020)
Thesis (MEng)--Stellenbosch University, 2020.